LDL-conjugated to GM1 micelles incorporating anticancer drugs to improve tumor cell uptake - Garro, Ariel Gustavo (2021)
Objective(s): The role of lipoproteins (LDL) as active molecules with preferential tumor interaction, but limited drug delivery capacity, has been previously reported. On the other hand, in a previous report, we demonstrated the high capacity of monosialogangliosides (GM1) micelles as drug transporters. Materials and Methods: In this work, GM1 was loaded with high doses of oncologic drugs such Paclitaxel or Doxorubicin and binded to LDL lipoproteins to form GM1-drug-LDLwater soluble complex. Evidence suggests that both, hydrophobic and electrostatic forces, participate in the interaction, regulated by conditions such as pH, temperature and ionic strength. Results: Results of DLS and TEM show that GM1-LDL complexes are considerably larger than the sum of their individual compounds, with a high charge of electronegative surface (-55.9 mV). In addition, the cytotoxic effect on cell cultures is greater when drugs are contained in GM1-LDL complexes than when loaded in GM1 micelles. Conclusion: The results suggest the participation of active energy-dependent mechanism in the uptake of GM1-LDL drug, probably linked to the LDL receptor by the tumor cells. However, we could not confirm that the transport through LDL receptors is the only one that participates in the cellular uptake of the micelles.